PENERAPAN PRINSIP EKONOMI SYARIAH DALAM INDUSTRI KEUANGAN GLOBAL: SEBUAH KAJIAN LITERATUR - Gani, Ahmad Abdul (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2022)
This scientific article attempts to explore and understand how Islamic economic principles are applied in the global financial industry. In the context of globalization and global economic integration, this analysis is becoming increasingly important, along with increasing demand and rapid growth in the Islamic finance sector. This article uses the literature review method to explore various previous studies and relevant literature. In this regard, this article discusses the basic concepts of Islamic economics, Islamic financial principles and instruments, and how these principles are applied and practiced in the global financial industry. Furthermore, this article evaluates the extent to which Islamic economic principles can make a positive contribution to stability and fairness in the global financial system. The findings from this study indicate that the application of sharia economic principles can help create a more stable, fair and sustainable financial system. In addition, this article also identifies some of the challenges and obstacles in applying these principles and offers some recommendations for further research in this area.